CHALLENGES IN BUILDING LEARNING ORGANIZATION IN MALAYSIA - Ahmad, Abd Rahman; Musa, Kamarudin (International Business Education Journal, 2013)
Challenges are seen as a sign that building learning organization requires a consistent effort and one has to be committed enough to make sure that everything is working right. There is no simple way to build a learning organization. Each organization must develop a structure and style that is best suited for its own people, history, skill base, technology, mission, and culture. The objective of this paper was to highlight the study of the challenges in building a learning organization that has been conducted in selected Malaysian organizations. Three organizations were selected for this study. The nature of the organizations varies based on their own functions. The study was conducted by means of qualitative research methodology. This means that the focus was to understand an event and its interaction within the natural context in order to determine what and how the challenges faced by the selected organizations in building a learning organization. The study found that the challenge faced by the selected organizations in a building of learning organizations are varied and indicates some evolving elements. It was observed that the elements of challenges are interpreted based on the organization’s own identity. It can be concluded that the study had identified the elements of challenges in building a learning organization. It also provides some guidelines to enable the organizations’ concern to develop into a full-fledged learning organization. The study implies that each organization has different challenges in building to be a learning organization. Therefore, it is necessary to develop ways of identifying challenges while building learning organizations.